ПРОФЕСІЙНА ІДЕНТИФІКАЦІЯ МАЙБУТНЬОГО ВЧИТЕЛЯ - Sokolova, Iryna (Continuing Professional Education: Theory and Practice, 2019)
Professional identification of future teachers at the university is a personalized process of his professional identity formation. The article outlines the professional human identification features. It has been grounded that social and occupational stratification, occupational status, formed professional competence is the result of the future teacher’s professional identification in high school. Teacher’s professional identity is a product of his personal and professional development throughout life.